Nanocellulose-alginate hydrogel for cell encapsulation. (13th February 2015) - Park, Minsung; Lee, Dajung; Hyun, Jinho
Highlights: Bio-nanocomposites improved the properties of hydrogel for cell encapsulation. The compression strength and chemical stability of the biocomposites were increased. The 3D fibrous contribution of TOBC enhanced the viability of cells encapsulated. The proliferation of the cells was enhanced in bionanocomposites. We report a potential candidate for the encapsulation of cells, such as β-cell islets. Abstract: TEMPO-oxidized bacterial cellulose (TOBC)-sodium alginate (SA) composites were prepared to improve the properties of hydrogel for cell encapsulation. TOBC fibers were obtained using a TEMPO/NaBr/NaClO system at pH 10 and room temperature. The fibrillated TOBCs mixed with SA were cross-linked in the presence of Ca 2+ solution to form hydrogel composites. The compression strength and chemical stability of the TOBC/SA composites were increased compared with the SA hydrogel, which indicated that TOBC performed an important function in enhancing the structural, mechanical and chemical stability of the composites. Cells were successfully encapsulated in the TOBC/SA composites, and the viability of cells was investigated. TOBC/SA composites can be a potential candidate for cell encapsulation engineering.